1992
DOI: 10.1901/jeab.1992.57-267
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the Fine Structure of Schedule‐controlled Behavior

Abstract: The variability in the behavioral equilibrium established by six basic schedules was characterized. The measures were the pause preceding the first response in each interreinforcement interval; the mean rate of responding in each interreinforcement interval; and the relative frequency of each interresponse time. The temporal windows ranged across the 780-session exposure, across a session, and across the interreinforcement interval. A display of individual interresponse times as a function of time in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 19 publications
3
65
0
Order By: Relevance
“…Information on other behaviors occuring will provide empirical support for the tracking hypothesis and may explain two effects of the signals: the irreversibility of the effect on the response rate and the facilitation of the temporal discrimination observed in some conditions. In addition, further research with more finely grained analyses of the responding, such as IRT analysis (e.g., Gentry, Weiss, & Laties, 1983;Palya, 1992;Shull & Brownstein, 1970;Staddon & Frank, 1975), might shed more light on the process of the complex signal effects observed here.…”
Section: Discussionmentioning
confidence: 95%
“…Information on other behaviors occuring will provide empirical support for the tracking hypothesis and may explain two effects of the signals: the irreversibility of the effect on the response rate and the facilitation of the temporal discrimination observed in some conditions. In addition, further research with more finely grained analyses of the responding, such as IRT analysis (e.g., Gentry, Weiss, & Laties, 1983;Palya, 1992;Shull & Brownstein, 1970;Staddon & Frank, 1975), might shed more light on the process of the complex signal effects observed here.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, an initial shortduration rate decrease at the session onset, as well as a slow steady rate increase across the entire session, has been shown (Palya, 1992).…”
mentioning
confidence: 98%
“…The current practice of collapsing data across a session into a single index indicates that the bitonic effect either had not been noticed, or had not been considered significant by most researchers before McSweeney's 1992 observation. Moreover, studies explicitly depicting behavior as a function of time in the session have not always shown the bitonic effect (McSweeney et al, 1990;Palya, 1992).There is also variability in the magnitude ofthe withinsession rate change. It is very strong in some circumstances, most notably in rats on pseudomultiple schedules with high reinforcement rates and session lengths which result in a substantial number ofreinforcers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, PRPs increased within a session on FI and differential-reinforcementof-low-rate schedules while local response rates showed the opposite pattern. McSweeney et al (1994) noted that previous studies of PRPs on FI schedules showed either no change (Palya, 1992) or increases (Collier, 1962) in pauses.…”
mentioning
confidence: 95%